2013
DOI: 10.1002/jwmg.502
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐region response to conservation buffers targeted for northern bobwhite

Abstract: We coordinated a large‐scale evaluation of northern bobwhite (Colinus virginianus) population response to establishment of 9‐m to 37‐m linear patches (buffers) of native herbaceous vegetation along row‐crop field margins as part of the Conservation Reserve Program practice Habitat Buffers for Upland Birds (CP33). We compared northern bobwhite covey densities on 1,088 paired row‐crop fields with and without native herbaceous buffers in 13 states during autumn, 2006–2008. We used a 2‐stage random effects modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…; Evans et al . ). Buffered agricultural fields were selected randomly from a sampling frame of CP33 contracts in each participating state ( n ≥ 40 per state).…”
Section: Methodsmentioning
confidence: 97%
“…; Evans et al . ). Buffered agricultural fields were selected randomly from a sampling frame of CP33 contracts in each participating state ( n ≥ 40 per state).…”
Section: Methodsmentioning
confidence: 97%
“…Dickcissels are grassland specialists found frequently on CRP land [27,28]. Dickcissel density in buffers adjacent to developed areas did not differ from buffers adjacent to grassland habitat.…”
Section: Discussionmentioning
confidence: 87%
“…Evans et al . ). Conover, Burger & Lindner () showed that field buffers increased nesting activities along field margins for a range of birds, including indigo buntings.…”
Section: Discussionmentioning
confidence: 97%
“…The National CP‐33 Monitoring Program coordinated by the Mississippi State University, Department of Wildlife, Fisheries, and Aquaculture was set up to monitor beneficial effects of herbaceous buffers around agricultural fields on bird densities in several Southeastern and Midwestern states (Evans et al . ). To set up a monitoring scheme, a minimum of 40 CP‐33 contracts per state were randomly selected from all CP‐33 contracts.…”
Section: Methodsmentioning
confidence: 97%